The Effect of Green Marketing Mix, Environmental Awareness and Green Innovation on Green Purchase Intention - Andika, Jiva; Nuvriasari, Audita (LifeSciFi, 2024)
This research aims to examine the impact of Green Marketing Mix, Environmental Awareness, and Green Innovation on Green Purchase Intention for Wardah Cosmetics. The study involved 100 respondents, selected using a purposive sampling technique. Through multiple linear regression analysis and hypothesis testing using the t-test, the results reveal the Green Marketing Mix does not have a significant positive effect on the intention to purchase Wardah's environmentally friendly products. This suggests that while Wardah may be incorporating green marketing elements into its strategies, these efforts alone are not a decisive factor in influencing consumers’ buying intentions toward eco-friendly products. Environmental Awareness shows a significant positive impact on consumers' intention to buy Green Wardah Cosmetics. This indicates that individuals who are more conscious of environmental issues are more likely to be motivated to purchase products that align with their ecological values, demonstrating the importance of environmental concern in shaping green purchase behavior. Green Innovation also has a significant positive influence on Green Purchase Intention. This suggests that Wardah’s efforts to innovate in sustainable ways, such as using environmentally friendly ingredients or packaging, resonate with consumers and positively affect their decision to buy.